The role and response of primary healthcare services in the delivery of palliative care in epidemics and pandemics: a rapid review to inform practice and service delivery during the COVID-19 pandemic - Mitchell, S; Maynard, V; Lyons, V; Jones, N; Gardiner, C (SAGE Publications, 2020)
Background: The increased number of deaths in the community happening as a result of COVID-19 has caused primary healthcare services to change their traditional service delivery in a short timeframe. Services are quickly adapting to new challenges in the practical delivery of end of life care to patients in the community including through virtual consultations and in the provision of timely symptom control.